Minimally Invasive Surgery in Orthopedics - Scuderi, Giles R.; Tria, Alfred J. (Springer International Publishing : Imprint: Springer, 2016)
Now revised and expanded into a major reference work, Scuderi and Tria bring together leaders in the field for this update of their classic 2010 text on minimally invasive surgery in orthopedics. Organized anatomically, each section has been reviewed and revised with the most current information and techniques, both common and complex. An entirely new section on analgesics and anesthesia is included, and the former section on the upper extremities is split into three distinct sections on the shoulder, elbow, and hand, respectively, for a more in-depth presentation of these areas. Subsequent sections on the hip, knee, foot and ankle, and spine are similarly reinforced with the state-of-the-art for each region. The final section is reworked to include not only computer navigation strategies but other innovative technologies in MIS as well. Now, as then, this is the go-to reference for orthopedic surgeons, residents and fellows seeking a practical understanding of minimally invasive techniques in orthopedics. .